The Effect of 5E-Learning Cycle Model Using Animation Media on the Learning Activity and Learning Outcomes of Students in Senior High School Class XI on Salt Hydrolysis Material - Iqbal, M; Mawardi, Mawardi (Proceedings Series on Physical & Formal Sciences, 2022)
The aim of this study is to determine the effect of learning model 5E learning cycle on learning activities and student learning outcomes on salt hydrolysis material. The research was conducted at Senior High School (SMA) Negeri 10 Medan. This research used research design of Pretest-posttest control group design. The sample was taken by purposive sampling technique and the obtained sample consist of 2 class which is: XI IPA 2 as an experimental class and XI IPA I as a control class. In the experimental class was taught used learning model 5E learning cycle using animation media and in control, class was taught using direct instruction model using animation media. The research instrument used the objective test in form of multiple choice questions as many as 25 questions, which previously passed through validation test, difficulty test, the test of different power, and reliability test with reliability value 0,91. Data analysis in this study used parametric inferential statistical analysis method, which the pretest and normalized score data had to pass normality and homogeneity test. X2count the pretest and gain score in the two study classes is greater than X2table and F-count the pretest and gain score in both the research class is greater than F-table. The research hypothesis was tested using statistical right-tailed t-test. Based on the calculation of t-statistical using right-tailed t-test obtained t-count results 4.29 and t-table at the 0.05 significance level 1.99. Furthermore, by t-count> t-table implied that the results of this study indicate there is influence of learning model of learning cycle 5E using animation media to the student learning outcomes in SMA of class XI on salt hydrolysis and student learning activity taught by learning model 5E learning cycle using animation media equal to 64,88%, higher than the student learning activity taught by direct instruction model using animation media that is equal to 55,72%.